The Alpha Generation and Its Role in Islamic World Civilization - Shofiy Adilah ‘Afaf; Muthoifin (Solo International Collaboration and Publication of Social Sciences and Humanities, 2024)
This research investigates the role of Generation Alpha, which was born in 2010 and is fully integrated with the digital age, in the context of the civilization of the Islamic world. With rapid technological advancements, this generation has the unique potential to bring significant changes in various aspects of life, including in the context of the civilization of the Islamic world. This study aims to identify and analyze how the unique characteristics of Generation Alpha, particularly within the Muslim community, can influence, strengthen, and even transform Islamic values in the face of the challenges of modernity and globalization. Using a mixed methodology involving quantitative, and qualitative surveys, in-depth interviews, and literature studies, the study collected data from different countries with significant Muslim populations. The results show that Generation Alpha has a strong tendency towards the use of digital technology in religious practices, education, and social interaction, which offers new opportunities for Islamic education and da'wah. However, challenges also arise related to maintaining traditional Islamic values in the fast-paced digital era.